2004
DOI: 10.1007/s00467-003-1381-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of gentamicin on urinary electrolyte excretion in neonates

Abstract: It has recently been shown that a single dose of gentamicin causes immediate and transient calcium and magnesium renal wasting in adults. The aim of this study was to determine the acute effect of gentamicin administration on renal electrolyte handling in preterm and full-term neonates. Twenty-three neonates treated with gentamicin for suspected infection were enrolled in the study. Serum and 3-h urine electrolytes were measured before and immediately after gentamicin infusion on the 1st, 3rd, 4th, and 7th day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 13 publications
1
23
3
1
Order By: Relevance
“…There are several other factors that may affect serum calcium during the early period after birth. Persistent urinary calcium and magnesium wasting after gentamicin treatment (2.5 mg/kg/ 12 h) in neonates has been reported by Giapros et al [21], although in their study, serum electrolyte levels were normal. Whether the differences in serum calcium levels between these two reports are related to different doses of gentamicin remains unclear.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…There are several other factors that may affect serum calcium during the early period after birth. Persistent urinary calcium and magnesium wasting after gentamicin treatment (2.5 mg/kg/ 12 h) in neonates has been reported by Giapros et al [21], although in their study, serum electrolyte levels were normal. Whether the differences in serum calcium levels between these two reports are related to different doses of gentamicin remains unclear.…”
Section: Discussionmentioning
confidence: 62%
“…Both clinical observation and experimental animal studies have demonstrated that acute gentamicin administration produced significant urinary calcium and magnesium wasting [4,20,21]. As mentioned earlier, gentamicin can cause symptoms and signs identical to the Bartter syndrome type 5, which is due to a gain of function mutation of the CSR [22].…”
Section: Discussionmentioning
confidence: 99%
“…Gentamicin has been reported to be an effective drug for various applications in neonatal intensive care units [1][2][3][4][5][6][7], but also to be one which is relatively toxic, with indications that it can induce tubular injury in term and preterm neonates [1][2][3][4]. The dosing schedules in this age group are also subject to controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a cumulative effect of gentamicin was observed. [10][11][12] We found an increase in urinary calcium excretion after the first dose of gentamicin, and an even higher increase after the second dose of gentamicin. A previous study showed that serum calcium levels were lowest on third day of gentamicin.…”
Section: Discussionmentioning
confidence: 56%